The war in Ukraine and changes in the global economic system - Dimitrijević, Bojan; Dželetović, Milenko (Sociološki pregled, 2022)
The US years-long irresponsible policy with the excessive printing of dollars, reinforced by the COVID-19 crisis and the war in Ukraine, has led to a large public debt and increasing inflation in the US, which significantly threatens the position of the dollar as the world’s reserve currency. The latest challenge to the dollar came from Russia, China and the BRICS countries. The paper analyzes the consequences of the war in Ukraine, the sanctions-based war between Russia and the West, the position of the dollar as the world’s reserve currency and the weaknesses of the international financial-monetary system leading to financial instability, frequent crises and growing inequality. A special emphasis has been placed on possible reforms of global finances and alternative proposals for a new reserve currency and more efficient work of global economic institutions (IMF) with the aim of achieving greater equality and faster economic growth.